2000
DOI: 10.1042/bj3520277
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low-density lipoprotein impairs the anti-coagulant function of tissue-factor-pathway inhibitor through oxidative modification by its high association and accelerated degradation in cultured human endothelial cells

Abstract: We have examined whether oxidized low-density lipoprotein (ox-LDL) affects the function of tissue-factor-pathway inhibitor (TFPI), an anti-coagulant regulator in the extrinsic pathway of coagulation, in cultured human umbilical vein endothelial cells (HUVEC). Treatment of culture medium of HUVEC with ox-LDL, but not with native or acetylated LDLs, drastically decreased the reactivity of TFPI to its antibody specific for Kunitz domain 1 or one specific for the conformation between Kunitz 1 and 2 of TFPI, and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The administration of recombinant TFPI or of the TFPI gene into animal models has demonstrated that TFPI is a useful anticoagulant for preventing the thrombogenicity of vascular wall cells. The relationship of TFPI with oxidized LDL 76,77 and with Lp(a) 78 has been demonstrated.…”
Section: Potential Roles Of Tfpi In Atherogenesismentioning
confidence: 99%
“…The administration of recombinant TFPI or of the TFPI gene into animal models has demonstrated that TFPI is a useful anticoagulant for preventing the thrombogenicity of vascular wall cells. The relationship of TFPI with oxidized LDL 76,77 and with Lp(a) 78 has been demonstrated.…”
Section: Potential Roles Of Tfpi In Atherogenesismentioning
confidence: 99%
“…fatty acid and cholesterol [1] , leads to the formation of foam cells (macrophages laden with cholesterol) and interferes with the activity of an endothelial coagulation inhibitor [through modification and degradation of tissue factor (TF) pathway inhibitor], thereby promoting local coagulation [2] .…”
mentioning
confidence: 99%
“…Recently Ettelaie et al (19) reported that the TFPI-dependent inhibition of TF activity was reduced when a mixture of LDL and rTFPI or TFPI derived from Hep G2 cells, not derived from plasma, was oxidized, and they suggested that the oxidation of LDL might mask lysine and arginine residues within the Kunitz domains of TFPI. We have shown that free TFPI derived from human umbilical vein endothelial cells or rTFPI associates with ox-LDL, but not with native or acetylated LDL, and we proposed that association between TFPI and ox-LDL might cause structural alteration of the TFPI molecule, leading to impairment of inhibitory activity on FX activation (20). In order to understand the physiological function of TFPI under pathological conditions, such as increase in oxidation of LDL in plasma and in the vascular bed, it is important to establish the precise mechanism of the association of TFPI with ox-LDL.…”
Section: Introductionmentioning
confidence: 94%
“…LDL and oxidized LDL were prepared as described previously (20). Briefly, LDL was incubated with 10 M CuSO 4 for 12 h at 37°C and 200 M EDTA was added.…”
Section: Modification Of Ldlmentioning
confidence: 99%